1998
DOI: 10.1007/s11664-998-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Induced Yellow Luminescence in GaN Grown by Halide Vapor Phase Epitaxy

Abstract: Strong yellow luminescence (YL) was found in GaN grown by the halide vapor phase epitaxy technique, using an NH 3 -HCl-GaCl-N 2 -H 2 growth chemistry. The low-temperature (less than 100K) thermal activation energy of the yellow luminescence was determined to be ~18 meV, which indicates that a shallow donor, rather than a 'shallow' acceptor, was involved in observed radiative transition. The temperature dependence of the YL peak energy and the shape of the YL band imply that there are multiple recombination cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
4
6
0
Order By: Relevance
“…5 is interpreted as a decrease in the radiative efficiency of the YL band. A similar decrease in the YL intensity in the range 10-100 K was reported in n-type GaN by Zhang and Kuech, 13 who proposed ionization of shallow donors as the reason for the reduction in YL efficiency (assuming a DAP-type transition). Regardless of the origin of this effect, the differences between Figs.…”
Section: Resultssupporting
confidence: 81%
“…5 is interpreted as a decrease in the radiative efficiency of the YL band. A similar decrease in the YL intensity in the range 10-100 K was reported in n-type GaN by Zhang and Kuech, 13 who proposed ionization of shallow donors as the reason for the reduction in YL efficiency (assuming a DAP-type transition). Regardless of the origin of this effect, the differences between Figs.…”
Section: Resultssupporting
confidence: 81%
“…III D͒ indicates that H is also involved in a complex giving rise to a luminescence band in the yellow spectral region. This result is consistent with previous reports by Zhang and Kuech, 20,22 who have shown that an introduction of H during GaN crystal growth results in a strong YL band with properties ͑such as temperature dependence of photoluminescence intensity͒ different from those of the C-related YL band. However, at this stage, the microscopic model for the H-related complex which gives rise to the above H-related YL band is not clear, and this issue requires additional systematic studies.…”
Section: E Chemical Origin Of Ylsupporting
confidence: 93%
“…First of all, a number of reports, including this one, show that the chemical origin of YL is not simple, which may explain the apparent contradiction and complexity of the results on the properties of YL reported in the literature. 1 In agreement with previous reports, 20,22,25,34 our data shows that YL consists of several ͑at least two: Hand C-related͒ luminescence bands overlapping in the same spectral region. Hence several radiative recombination channels contribute to the YL band.…”
Section: E Chemical Origin Of Ylsupporting
confidence: 92%
See 1 more Smart Citation
“…The YL band itself often appears to be a compound peak containing several broad peaks that can merge into the broad defect luminescence often noted. 31,32 …”
Section: Figmentioning
confidence: 99%